2014
DOI: 10.1080/00268976.2014.931602
|View full text |Cite
|
Sign up to set email alerts
|

The Renner–Teller effect observed in the and electronic states of H2S+

Abstract: In 1995, Balzer et al. recorded a well-resolved photoelectron spectrum of the outer valence region of H 2 S between 12.7 and 14.5 eV. The vibronic energies were identified with the aid of calculated ionisation potentials. Following on from this, vacuum ultraviolet pulsed-field ionisation spectroscopy was used by Hochlaf et al. in 2004 to record partially resolved rotational spectra of H 2 S + . Finally, in 2010, Han, Kang and Kim recorded rotationally resolved electronic spectra of theà 2 A 1 −X 2 B 1 transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3] Specially, H 2 S + , as the simplest sulfur containing molecular ion, not only is an indispensable reaction intermediate in the combustion process, but also has a relevant role in the formation of molecules. Because of the possible roles in interstellar-cloud chemistry, [4][5][6] a lot of researches about H 2 S + have been done over the past years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Specially, H 2 S + , as the simplest sulfur containing molecular ion, not only is an indispensable reaction intermediate in the combustion process, but also has a relevant role in the formation of molecules. Because of the possible roles in interstellar-cloud chemistry, [4][5][6] a lot of researches about H 2 S + have been done over the past years.…”
Section: Introductionmentioning
confidence: 99%
“…Using the mass-analyzed threshold ionization photofragment excitation technique, Han et al [11] studied the rotationally resolved spectroscopy of the Ã2 A 1 ← X2 B 1 transition of H 2 S + , and found that the further photoexcitation can lead to the H 2 S + → H 2 + S + dissociation. In 2014, Duxbury et al [6] connected different methods to give a detailed description of the relation among different types of spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Ng and co-workers presented the photoelectron spectrum of H 2 S with the upgraded spectral resolution using the pulsed-field ionization technique combined with the vacuum ultraviolet synchrotron radiation source, providing the quantitatively refined data for the vibronic term values associated with the photoionization processes that produce H 2 S + in different electronic states of X 2 B 1 , A 2 A 1 , or B 2 B 2 . Ashfold and colleagues then reported the velocity map ion imaging results of the photodissociation of H 2 S + that reveal the unique role of nuclear spin on the photodissociation; the Renner-Teller coupling and spin–orbit coupling have also been found to play an important role in the dissociation process. , In 2014, Duxbury et al combined various types of spectroscopies to present a detailed description of the Renner-Teller effect in the A 2 A 1 and X 2 B 1 of H 2 S + . The theoretical investigation of H 2 S + was mainly focused on stationary-point electronic structure calculations for the lowest several electronic states and/or two-dimensional potential energy curves with one degree of freedom fixed at a specific value.…”
mentioning
confidence: 99%
“…24,25 In 2014, Duxbury et al combined various types of spectroscopies to present a detailed description of the Renner-Teller effect in the A 2 A 1 and X 2 B 1 of H 2 S + . 26 The theoretical investigation of H 2 S + was mainly focused on stationary-point electronic structure calculations for the lowest several electronic states and/or two-dimensional potential energy curves with one degree of freedom fixed at a specific value. The early study of Hirsch and Bruna 27 the conical intersection between A 2 A 1 and the higher B 2 B 2 state by performing multireference configuration interaction calculations.…”
mentioning
confidence: 99%